Data acquisition system for X‐ray free‐electron laser experiments at SACLA. (16th April 2015) - Joti, Yasumasa; Kameshima, Takashi; Yamaga, Mitsuhiro; Sugimoto, Takashi; Okada, Kensuke; Abe, Toshinori; Furukawa, Yukito; Ohata, Toru; Tanaka, Ryotaro; Hatsui, Takaki; Yabashi, Makina
<x xml:space="preserve">Abstract</x> A data acquisition system for X‐ray free‐electron laser experiments at SACLA has been developed. The system has been designed for reliable shot‐to‐shot data storage with a high data stream greater than 4 Gbps and massive data analysis. Configuration of the system and examples of prompt data analysis during experiments are presented. Upgrade plans for the system to extend flexibility are described.